Toxicological and histopathological evaluations of the effects if synthetic hormones - 17a-Ethinylestradiol and Levonorgestrel - on tilapia (Oreochromis niloticus) - Espiritu, Emilyn Q. (Transactions of the National Academy of Science and Technology, 2011)
Due to incomplete removal in most conventional biological sewage treatment plants, human excretions containing synthetic hormones from birth control pills find their way into sewage, agricultural runoff, and surface waters. In sufficiently high concentrations, these can affect the physiology and reproductive functions of exposed organisms. Unfortunately, information on their potential effects mostly comes from temperate habitats, thus, limiting their application to tropical environments. Acute toxicity tests (i.e. 96 hrs) and histopathological analyses of gills and liver tissues were performed to determin the effects of varying concentration of 17a-Ethinylestradiol (EE2) and Levonorgestrel on juvenile Oreochromis niloticus (i,e. "Tilapia"). Fish mortality increased as toxicant concentration and exposure period increased with Mean 96-hr LC50s±S.D. of 0.47±0.062 mg/L for EE2 and 6.03±1.03 mg/L for Levonorgestrel (p=0.05). Histopathological examinations also showed massive cellular damage - e.g. disorganization of lamellae, epithelium hyperplasia and hypertrophy, and blood congestion in gill tissues as well as nuclear hypertrophy, cytoplasmic vacuolation, and cytoplasmic degeneration in the liver - relative to the controls. The information generated in the study can be used as an aid in establishing proper waste water protocols, in risk and impact assessments of xenoestrogens and in policy formulation for public health and the environment.